A kind of high purity quartz sand and preparation method thereof
By heating the hydrolysis reaction under alkaline conditions and combining ion exchange, acid solution treatment, refrigeration centrifugation, vacuum microwave drying and chlorination roasting, the problems of high-purity quartz sand preparation cost, low yield and difficult to remove impurities in the prior art have been successfully solved, and a high-purity and low-cost quartz sand preparation is achieved.
Patent Information
- Application Number
- CN202510024671.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-08
AI Technical Summary
It is difficult to efficiently prepare high-purity quartz sand in the prior art, especially products with purity of 4N8 and above, and the purification cost of natural ore is high, low yield, and impurities are difficult to remove.
Silicone sludge is prepared evenly by stirring, and then the hydrolysis reaction is heated under alkaline conditions, and additives and dispersants are added to promote the reaction. Then ion exchange, acid solution treatment, refrigeration centrifugation, vacuum microwave drying and chlorination roasting are carried out to obtain high-purity quartz sand.
It has achieved the preparation of high-purity quartz sand, with a purity of 6N9 level, a uniform and controllable particle size, low cost, high yield and high yield. It is suitable for high-tech industries such as photovoltaics and semiconductors.
Smart Images

Figure CN119430204B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of quartz sand preparation and relates to high-purity quartz sand and a preparation method thereof. Background Art
[0002] High-purity quartz sand is a non-metallic mineral raw material with a SiO2 content of over 99.95%. It possesses excellent physical and chemical properties, such as high-temperature resistance, corrosion resistance, low thermal expansion, high insulation, and light transmittance. Demand for high-purity quartz sand is rapidly growing in the photovoltaic and semiconductor sectors, particularly for products with a purity of 4N5 or higher. Semiconductor products have high purity requirements, typically requiring quartz sand with a purity of 4N8 or higher. In the photovoltaic industry, high-purity quartz sand, used as a raw material for the manufacture of quartz crucibles, provides important support for the production of monocrystalline silicon. Demand for this sand continues to grow with the increase in new photovoltaic capacity.
[0003] Currently, the main source of quartz sand on the market is purified from natural ores. Due to the complex composition and structure of the ore, it is difficult to purify ordinary quartz ore to above 99.99%. High-purity quartz sand can only be obtained by purifying clean natural crystals produced by a few mineral veins. However, the limited resources of such mineral veins restrict the production of ultra-high-purity quartz sand. Quartz sand on the market often contains impurity ions such as Al, Ti, and Fe. These ions exist in the quartz lattice in an isomorphic form and are difficult to completely remove through physical methods. At the same time, gas-liquid inclusions are also common impurities in quartz. They have a significant impact on the purity of quartz sand and are difficult to remove.
[0004] Therefore, it is of great significance to explore a method for synthesizing high-purity quartz sand to solve the problems of high cost and low yield of quartz sand prepared by purifying natural crystals in the current market, and the difficulty in removing impurities and gas-liquid inclusions. Summary of the Invention
[0005] To solve the above technical problems, the present invention provides a high-purity quartz sand and a preparation method thereof. The method uses water, mixed alkali, and silicon powder as raw materials. Based on the raw material ratio, silicon powder and water are mixed at a mass ratio of 1:0.6 to 1.6, and then additives are added and stirred evenly to prepare silicon mud. The remaining water and mixed alkali in the raw materials are added to a reactor and heated. Subsequently, the silicon mud is added to the reactor in batches to react to obtain a sodium silicate solution. The sodium silicate solution is removed from anions and cations, and then an acid solution is added and heated to obtain a silicic acid gel. The silicic acid gel is centrifuged and frozen. After thawing, it is vacuum-microwave dried and chlorinated and roasted to obtain high-purity quartz sand. The purity of the quartz sand synthesized by the present invention reaches 6N9 level, and the particle size is uniform and controllable. The present invention provides a low-cost, high-yield, and high-yield high-quality quartz sand preparation method for photovoltaics, semiconductors, and other fields.
[0006] To achieve the technical purpose of the present invention, on the one hand, the present invention provides a high-purity quartz sand and a preparation method thereof, which specifically comprises the following steps:
[0007] S1: Water, mixed alkali and silicon powder are weighed in a mass ratio of 17~25:1:0.7~1.4 to obtain the total raw material, and 1~5wt% of the LQ-TJ69 additive of the total raw material is weighed. Based on the ratio of the total raw material, silicon powder and water are mixed in a mass ratio of 1:0.6~1.6, and then the LQ-TJ69 additive is added and mixed evenly to prepare silicon mud.
[0008] S2: Add the remaining water and mixed alkali in the total raw materials to the reactor and heat with stirring. When the temperature of the reactor reaches the reaction temperature range of 60~80℃, add the silicon mud to the reactor in batches, wait for the reaction and slowly add the next batch until all the silicon mud is added. Stir and heat for 4~8 hours from the beginning to the end of the reaction. When no bubbles are released during the reaction, introduce nitrogen for 40~60 minutes and perform ultrasonic treatment at the same time. The ultrasonic power is 600W and the ultrasonic frequency is 40kHz. Then filter to obtain a high-purity sodium silicate solution.
[0009] S3: 0.5~3wt% of LQ-FS69 dispersant of the total raw materials is added to the sodium silicate solution obtained in S2 and stirred evenly. Then, the solution is passed through a continuous series ion exchange column to first remove inorganic impurities, and then through an ion exchange column to remove alkali metal impurities.
[0010] S4: Mix a mixed acid and water in a mass ratio of 1:10-14 to obtain a mixed acid solution. Pour the mixed acid solution into the sodium silicate solution passed through the continuous series ion exchange column in S3, stirring continuously during the pouring process. Stirring is stopped after all the mixed acid solution is poured in. The mass ratio of the sodium silicate solution, acid, and water is 8.5-10.5:1:10-14. Heat the solution to 60-85°C for 2-5 hours to obtain a silicic acid gel.
[0011] S5: Place the silica gel in a vacuum refrigerated centrifuge for freeze-thaw treatment. Centrifuge at 1600-2000 rpm for 20-30 minutes to remove moisture from the silica gel. Then, freeze the gel at a temperature of -20--13°C, a rotation speed of 500-800 rpm, and a vacuum of -0.06--0.1 Pa for 10-24 hours. Thaw the gel and centrifuge at 1600-2000 rpm for 30-40 minutes to remove the thawing moisture. Place the gel in a microwave vacuum drying oven at a vacuum of -0.1 Pa, a microwave power of 0.7 kW, and a temperature of 100-180°C for 5-15 hours to form particles. Sieve the gel to remove quartz sand particles larger than 100 μm and smaller than 50 μm.
[0012] S6: The screened quartz sand particles are subjected to chlorination roasting at a temperature range of 800-1000°C for 4-8 hours. After roasting, magnetic separation is performed to obtain quartz sand particles with high purity, few inclusions, and uniform and controllable particle size.
[0013] Specifically, the LQ-TJ69 additive is used to increase the reaction rate, and the LQ-FS69 dispersant is used to increase the fluidity of the solution. The addition of the LQ-TJ69 additive and the LQ-FS69 dispersant of the present invention can significantly promote the progress of the reaction. After adding the LQ-TJ69 additive, the reaction time in the reactor can be significantly reduced, and the proportion of residue in the reactor is significantly reduced, indicating that the addition of the LQ-TJ69 additive can significantly promote the hydrolysis reaction of silicon mud under alkaline conditions, the substrate silicon powder is completely converted into sodium silicate, and the reaction is more thorough.
[0014] Specifically, the mixed alkali in S1 is composed of sodium hydroxide, potassium hydroxide and tetramethylammonium hydroxide in a mass ratio of 0.8~1.2:0.8~1.2:0.2~0.5. Sodium hydroxide and potassium hydroxide have strong alkalinity and can promote the rapid occurrence of the initial reaction. Tetramethylammonium hydroxide helps to reduce the surface tension of water and can accelerate the reaction process. The ultrasound in S2 uses a probe-type ultrasonic instrument to remove oxygen from the system. The mixed acid in S4 is composed of hydrochloric acid and acetic acid in a volume ratio of 3:1. The chlorination roasting described in S6 uses hydrogen chloride gas.
[0015] Specifically, the present invention does not specifically limit the ion exchange column for removing inorganic impurities and alkali metal impurities in S3. Those skilled in the art can select the specific type of ion exchange column according to the type of impurities.
[0016] Specifically, the equipment for containing quartz sand in S1, S2, S4, and S5 is made of PTFE or PP to avoid the introduction of other impurities, and the container used for chlorination roasting is a quartz crucible.
[0017] In another aspect, the present invention claims protection for high-purity quartz sand produced by the above-described method for producing high-purity quartz sand. The high-purity quartz sand produced by the present invention is 6N9 grade, with a purity exceeding 99.9999%. It also significantly reduces the content of gas-liquid inclusions in the quartz sand, thereby improving its quality. The quartz sand produced by the present invention has a high yield rate, exceeding 80%. The quartz sand produced by the present invention has broad application prospects in high-tech industries such as electronics, optical fiber, and photovoltaics.
[0018] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages:
[0019] (1) The quartz sand preparation method of the present invention can obtain quartz sand particles with high purity, few inclusions, and uniform particle size. The quartz sand prepared by the present invention using industrial-grade silicon powder as raw material has a purity of 6N9 grade and an average particle size of 62.5~72.3μm. Compared with the quartz sand of the prior art, which can only reach the 4N9 grade, the purity has been significantly improved. The preparation method of the present invention can significantly reduce the content of gas-liquid inclusions in quartz sand and improve the quality of quartz sand. The quartz sand prepared by the present invention has broad application prospects in high-tech industries such as electronic information, optical fiber, and photovoltaic industries. The process path provided by the present invention can be scaled up and industrialized for production, and has the advantages of high yield, excellent product quality, low energy consumption, and low cost. The quartz sand preparation method provided by the present invention has a yield of more than 85% and an output rate of more than 94%.
[0020] (2) The present invention changes the state of the raw material silicon powder and combines the silicon powder with water and LQTJ-69 additive in a certain proportion to obtain silicon slurry, so that the hydrolysis reaction of the silicon powder under alkaline conditions occurs more rapidly and the reaction is more thorough. Through experiments, the present invention found that adding the LQ-TJ69 additive and preparing the silicon powder into silicon slurry can significantly reduce the reaction time in the reactor and significantly reduce the proportion of residue in the reactor. This shows that the technical solution can significantly promote the hydrolysis reaction of silicon slurry under alkaline conditions, and the substrate silicon powder is completely converted into sodium silicate, and the reaction is more thorough.
[0021] (3) The present invention can control the particle size of quartz sand by adjusting the concentration of the acid solution. The concentration of the acid solution has a significant impact on the particle morphology and particle size of the quartz sand. By directly affecting the acidity environment of the reaction system, it further affects the particle morphology and particle size of the synthetic quartz sand. Through experiments, the present invention found that the quartz sand particles prepared by the mixed acid solution with a mass ratio of acid to water of 1:12 have a concentrated particle size, a narrow range, and a particle size that better meets practical application requirements. In addition, the quartz sand contains fewer inclusions.
[0022] (4) The present invention adopts a combination of frozen centrifugation, freeze-thaw and vacuum microwave drying to dry the quartz sand particles, which reduces the appearance of inclusions during the synthesis process. The surface of the quartz sand obtained is smoother. Compared with conventional drying methods, energy consumption and construction period are greatly shortened. Compared with the scheme of directly drying the gel or freezing the gel and then drying it in an oven, the quartz sand particles obtained by the process of the present invention are smaller in size and more uniform in particle size, and the yield of quartz sand can be significantly improved.
[0023] (5) The present invention uses a mixed alkali obtained by mixing sodium hydroxide, potassium hydroxide, and tetramethylammonium hydroxide as one of the raw materials. Sodium hydroxide and potassium hydroxide have strong alkalinity and can promote the rapid occurrence of the initial reaction. Tetramethylammonium hydroxide helps to reduce the surface tension of water and can accelerate the reaction process. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Microscope image of the quartz sand prepared for Experiment 1.
[0025] Figure 2 Microscope image of quartz sand prepared for Experiment 2.
[0026] Figure 3 Scanning electron micrograph of the quartz sand prepared for Experiment 1.
[0027] Figure 4 Scanning electron micrograph of the quartz sand prepared for Experiment 2. DETAILED DESCRIPTION
[0028] The technical solutions of the present invention are now described with reference to the following examples. However, the present invention is not limited to the following examples. The experimental methods and detection methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0029] The silicon powder used in the present invention is industrial grade silicon powder, the pure water is industrial pure water, and the reagents are all chemically pure.
[0030] LQ-TJ69 additive and LQ-FS69 dispersant are both provided by Xi'an Bluebridge New Energy Technology Co., Ltd. The active ingredient of LQ-TJ69 additive is N , N -dimethylacetamide, pyridine, and tert-butylamine, with the active ingredients accounting for 1%, 1%, and 2% of the total volume respectively, and water is used as the solvent; the active ingredients of LQ-FS69 dispersant are composed of anhydrous ethanol and methylpentanol, with the active ingredients accounting for 3.2% and 0.8% of the total volume respectively, and water is used as the solvent.
[0031] Example 1
[0032] This embodiment provides a method for preparing high-purity quartz sand, which specifically includes the following steps:
[0033] S1: Weigh the total raw materials at a mass ratio of pure water: mixed alkali: silicon powder of 17-25:1:0.7-1.4. Weigh 1-5 wt% of the total raw materials with LQ-TJ69 additive. The mixed alkali consists of sodium hydroxide, potassium hydroxide, and tetramethylammonium hydroxide in a mass ratio of 0.8-1.2:0.8-1.2:0.2-0.5. Based on the total raw material ratio, mix the silicon powder and pure water in a mass ratio of 1:0.6-1.6, then add the LQ-TJ69 additive to prepare silicon sludge.
[0034] S2: Add the remaining pure water and mixed alkali in the total raw materials into the reactor and heat with stirring. When the temperature of the reactor reaches the reaction temperature range of 60~80℃, slowly add the silicon mud into the reactor in batches. Wait until the reaction is slow (fewer bubbles are generated) and add the next batch until all the silicon mud is added. The heating process lasts for 4~8 hours from the beginning to the end of the reaction. When no bubbles are released during the reaction, introduce nitrogen for 40~60 minutes and perform ultrasonic treatment at the same time. The ultrasonic power is 600W and the ultrasonic frequency is 40kHz. A probe-type ultrasonic instrument is used to remove oxygen from the system. The solution is then filtered to obtain a high-purity sodium silicate solution.
[0035] S3: Add 0.5~3wt% of LQ-FS69 dispersant of the total raw materials to the sodium silicate solution obtained in S2 and stir evenly. Then pass it through a continuous series ion exchange column to first remove trace and various inorganic impurities and some alkali metal ions (the model of the ion exchange resin is Kehaisi T-42), and then pass it through an ion exchange column for removing alkali metal impurities (the model of the ion exchange resin is Xi'an Lanxiao LHSI-10).
[0036] S4: Mix a mixed acid (hydrochloric acid and acetic acid in a volume ratio of 3:1) and water in a mass ratio of 1:10-14 to obtain a mixed acid solution. Pour the mixed acid solution into the sodium silicate solution passed through the ion exchange column in S3, stirring continuously during the addition process. Stirring is stopped after all the mixed acid solution has been added. The mass ratio of sodium silicate solution, mixed acid, and water is 8.5-10.5:1:10-14. Heat the solution to 60-85°C for 2-5 hours to obtain a silicic acid gel.
[0037] S5: Place the silica gel in a vacuum refrigerated centrifuge and centrifuge at 1600-2000 rpm for 20-30 minutes to remove moisture from the silica gel. Then, freeze it at a freezing temperature of -20--13°C, a rotation speed of 500-800 rpm, and a vacuum of -0.06--0.1 Pa for 10-24 hours. Then, thaw it and centrifuge it at 1600-2000 rpm for 30-40 minutes to remove the thawing moisture. Place it in a microwave vacuum drying oven at a vacuum of -0.1 Pa, a microwave power of 0.7 kW, and a temperature of 100-180°C, and dry it for 5-10 hours to form particles. Then, sieve it to remove quartz sand particles larger than 100 μm and smaller than 50 μm.
[0038] S6: The quartz sand particles after screening are subjected to chloride roasting (using hydrogen chloride gas) at a roasting temperature range of 800~1000℃ and a roasting time of 4~8h. After roasting, magnetic separation is performed to obtain quartz sand particles with high purity, few inclusions and uniform particle size.
[0039] This embodiment conducts a total of 3 groups of experiments and 3 groups of comparative experiments. The experimental parameters of experiments 1 to 3 and comparative experiments 1 to 3 are shown in Table 1. The experimental parameters of comparative experiment 1 are the same as those of experiment 1, with the following differences: no LQ-TJ69 additive and LQ-FS69 dispersant are added, the silicon powder and pure water in the total raw materials are not prepared into silicon mud in S1, and the silicon powder is directly added to the reactor in batches in S2. The experimental parameters of comparative experiment 2 are the same as those of experiment 1, with the following differences: the silicic acid gel obtained in S4 is frozen at -20°C and then dried in an ordinary oven. Comparative experiment 3 prepares quartz sand with reference to the technical solution of implementation example 3 in the patent application number 202110866870.7. The parameters of the quartz sand prepared in each experiment are shown in Table 2, the ICP impurity concentration test results of the quartz sand prepared in each experiment are shown in Table 3, and the microscope image of the quartz sand prepared in experiment 1 is shown in Table 3. Figure 1 As shown in the microscope image of the quartz sand prepared in Experiment 2, Figure 2 As shown in the scanning electron microscope image of the quartz sand prepared in Experiment 1, Figure 3 As shown in the scanning electron microscope image of the quartz sand prepared in Experiment 2, Figure 4 shown.
[0040] Table 1: Experimental parameters for preparation of high-purity quartz sand
[0041]
[0042]
[0043] Table 2: Parameters of quartz sand prepared in Experiments 1 to 3 and Comparative Experiments 1 to 3
[0044]
[0045] Note: Output rate is the ratio of actual output sample mass to theoretical output; finished product rate is the ratio of qualified mesh sample mass to total sample mass.
[0046] Table 3: ICP impurity concentration test results of quartz sand prepared in Experiments 1 to 3 and Comparative Experiments 1 to 3
[0047]
[0048] Depend on Figures 1 to 4 It can be seen that the quartz sand particles prepared by the present invention have a smooth surface without holes, few inclusions, and uniform particle size.
[0049] Table 2 shows that the concentration of the mixed acid solution significantly affects the particle size range of the quartz sand. Within the mixed acid to water mass ratio range of 1:10 to 14, the greater the amount of water added, the larger the quartz sand particle size. The mixed acid solution further influences the particle morphology and particle size of the synthetic quartz sand by affecting the acidity of the reaction system. In particular, quartz sand produced with a mixed acid solution with a mixed acid to water mass ratio of 1:12 exhibits a more concentrated particle size range, a smaller particle size range, and a particle size that better meets practical application requirements. Furthermore, the quartz sand contains fewer inclusions.
[0050] As can be seen from Table 2, the addition of LQ-TJ69 additive and LQ-FS69 dispersant, as well as the preparation of silica sludge by mixing silica powder with water and LQ-TJ69 additive can significantly reduce the reaction time in the reactor, and the proportion of residue in the reactor is significantly reduced, indicating that the addition of LQ-TJ69 additive can significantly promote the hydrolysis reaction of silica sludge under alkaline conditions, and the substrate silica powder is completely converted into sodium silicate, and the reaction is more thorough.
[0051] As shown in Table 2, the present invention first removes water from the silica gel, then freezes it, thaws it, and then centrifuges it to remove the water produced by thawing. The quartz sand particles are then dried in a microwave vacuum drying oven. This technical solution can significantly reduce the content of gas-liquid inclusions in the quartz sand, and the quartz sand has a smaller particle size and a more uniform particle size distribution. It can also significantly improve the yield of the quartz sand.
[0052] It can be seen from Tables 2 and 3 that within the parameter range of the quartz sand preparation method provided by the present invention, quartz sand particles with high purity, few inclusions and uniform particle size can be produced. The purity of the quartz sand particles reaches the 6N9 level, and the average particle size is 62.5~72.3μm. Compared with the quartz sand of the prior art, which can only reach the 4N9 level, the purity has been significantly improved.
[0053] The above embodiments and descriptions are merely descriptions of preferred embodiments of the present invention. The present invention is not limited to the above embodiments. Without departing from the spirit and scope of the present invention, various changes and improvements made to the technical solutions of the present invention by ordinary technicians in this field should fall within the scope of protection determined by the present invention.
Claims
1. A method for preparing high-purity quartz sand, characterized in that: include: Raw materials, the raw materials are water, mixed alkali and silicon powder; The mixed alkali is composed of sodium hydroxide, potassium hydroxide and tetramethylammonium hydroxide; The raw materials and additives are subjected to heating reaction to obtain a sodium silicate solution, anionic and cationic impurities are removed, a mixed acid solution is added, and the mixture is heated to obtain a silicate gel; The silicic acid gel is subjected to freezing, thawing, vacuum microwave drying, and then chlorination roasting to obtain quartz sand particles; The heating reaction comprises: mixing part of the water in the raw material with the silicon powder and the additive to form silicon mud, heating the remaining water and the alkali, and adding the silicon mud in batches after reaching the reaction temperature of the heating reaction; The active ingredients of the additive are N , N -dimethylacetamide, pyridine, and tert-butylamine, wherein the active ingredients account for 1%, 1%, and 2% of the total volume of the additive, respectively, and water is used as the solvent; The mixed acid solution is composed of mixed acid and water, and the mass ratio of the mixed acid to water in the mixed acid solution is 1:10-12; The mixed acid consists of hydrochloric acid and acetic acid, and the volume ratio of hydrochloric acid to acetic acid is 3:1; The temperature of the vacuum microwave drying is 100-180° C., the time of the vacuum microwave drying is 5-10 h, the vacuum degree of the vacuum microwave drying is -0.1 Pa, and the microwave power of the vacuum microwave drying is 0.7 kW; The temperature of the chlorination roasting is 800-1000°C.
2. The method for preparing high-purity quartz sand according to claim 1, characterized in that: In the silicon mud, the mass ratio of silicon powder to water is 1:0.6~1.6; The additive is added in an amount of 1-5% of the mass of the raw material.
3. The method for preparing high-purity quartz sand according to claim 2, characterized in that: In the raw materials, the mass ratio of water, mixed alkali and silicon powder is 17-25:1:0.7-1.4; In the mixed alkali, the mass ratio of sodium hydroxide, potassium hydroxide and tetramethylammonium hydroxide is 0.8-1.2:0.8-1.2:0.2-0.
5.
4. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The reaction temperature of the heating reaction is 60-80°C, and the heating reaction lasts for 4-8 hours from the start of heating to the end of the reaction; After the heating reaction is completed, nitrogen is introduced for 40 to 60 minutes, and ultrasonic treatment is performed at the same time; The power of the ultrasonic treatment is 600 W, and the frequency of the ultrasonic treatment is 40 kHz.
5. The method for preparing high-purity quartz sand according to claim 1, characterized in that: Before removing the anionic and cationic impurities, a dispersant is added to the sodium silicate solution, wherein the amount of the dispersant added is 0.5-3% of the mass of the raw material; The effective components of the dispersant are composed of anhydrous ethanol and methyl amyl alcohol, which account for 3.2% and 0.8% of the total volume of the dispersant respectively, and water is used as the solvent.
6. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The mass ratio of the sodium silicate solution to the mixed acid solution is 8.5-10.5:
1.
7. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The heating temperature of the silica gel obtained by heating is 60-85° C., and the heating time of the silica gel obtained by heating is 2-5 hours.
8. The method for preparing high-purity quartz sand according to claim 1, characterized in that: Before freezing, the silica gel is centrifuged at 1600-2000 rpm for 20-30 min; The freezing temperature is -20 to -13°C, the freezing time is 10 to 24 hours, and the centrifugal speed during the freezing process is 500 to 800 rpm; After thawing, centrifuge at 1600-2000 rpm for 30-40 min; The freezing and thawing are carried out under a vacuum condition of -0.06 to -0.1 Pa.
9. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The chlorination roasting time is 4 to 8 hours; The chlorination roasting uses hydrogen chloride gas.
10. A high-purity quartz sand, characterized in that: The high-purity quartz sand is prepared by the preparation method of high-purity quartz sand according to any one of claims 1 to 9, wherein the purity of the high-purity quartz sand is higher than 99.9999%.
Citation Information
Patent Citations
Preparation method of silica sol controllable in grain size
CN105731468A
Purification method of high-purity quartz sand with SiO2 purity more than or equal to 99.99%
CN110127708A
Method for preparing high-purity quartz sand from superfine silicon powder
CN115676842A